Acting as a benefit corporation and a B Corp to responsibly pursue private and public benefits: The case of Paradisi Srl (Italy) - Mara Del Baldo (International Journal of Corporate Social Responsibility (JCSR), 2019)
Benefit Corporations and B Corps represent alternative models of enterprise that bridge the for-profit and not-for-profit model (hybrid organizations). Italy is the first country outside the US to pass Benefit Corporation legislation and introduce the Società Benefit (Law No 208, 2015), namely for profit companies formally allowed by law to pursue a CSR mission, intended to achieve general and/or specific public benefits. Starting from these premises, the aim of this study is to evaluate the motivations for and benefits of becoming a B Corporation through an empirical case study focussed on an Italian small and medium-sized enterprise (Paradisi Srl) transformed into Benefit in 2016. Findings point out the efficacy of this choice taking into account the enhancement of a socially responsible commitment to CSR practices and the creation of a public benefit, as well as the improvements in accountability, transparency and stakeholder engagement.
Keywords: 650; Benefit corporation; B Corp; Public benefit; Società benefit; CSR; Italy